A research-based mantra for compassionate caring. (November 2017) - Terry, Louise; Newham, Roger; Hahessy, Sinéad; Atherley, Siobhan; Babenko-Mould, Yolanda; Evans, Marilyn; Ferguson, Karen; Carr, Graham; Cedar, S.H.
Abstract: Background: The United Kingdom introduced the Six C′s strategy to help address deficits in approaching nursing care in a compassionate and caring manner. Objective: To identify the book, article, poem, film or play that most influenced nurse educators' understanding of care and compassion and to articulate a clearer understanding of compassionate caring. Design: A qualitative study applying discourse analysis to respondents' questionnaires and their nominated narrative. Settings and Participants: 41 nurse educators working in 5 universities in the UK ( n = 3), Republic of Ireland and Canada participated. 39 items (10 books, 2 journal articles, 10 poems, 15 films and 2 plays) were nominated. Findings: The desire to understand others and how to care compassionately characterised choices. Three main themes emerged. Abandonment of, and failure to see, the suffering person was evident in 25 narratives. Connecting with others was shown in 25 narratives as being able to truly seeing the other person. Comforting others was supported by 37 narratives with examples of kindness and compassion. Conclusion: Published narratives are valuable in developing compassionate responses. An annotated list is provided with suggestions for educational uses to help develop compassionate caring in student nurses. Compassionate, caring nurses recognise that patients need them to: "See who I am; Be present with me; Do not abandon me." Highlights: Published narratives develop compassion. Compassion means seeing your patients. Compassion means being present. Compassion means not abandoning.